2013
DOI: 10.1371/journal.pone.0071667
|View full text |Cite|
|
Sign up to set email alerts
|

Prefabrication of 3D Cartilage Contructs: Towards a Tissue Engineered Auricle – A Model Tested in Rabbits

Abstract: The reconstruction of an auricle for congenital deformity or following trauma remains one of the greatest challenges in reconstructive surgery. Tissue-engineered (TE) three-dimensional (3D) cartilage constructs have proven to be a promising option, but problems remain with regard to cell vitality in large cell constructs. The supply of nutrients and oxygen is limited because cultured cartilage is not vascular integrated due to missing perichondrium. The consequence is necrosis and thus a loss of form stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 24 publications
0
43
2
Order By: Relevance
“…Color images available online at www.liebertpub.com/tea perichondrial layer were consistent with previous research, 3,6,10,12,23 and a continuous elastin network was found similar to only one other tissue-engineered ear study at a comparable time point. 23 In contrast to other long-term studies, auricular constructs at 6 months displayed no signs of osteophyte development, 6,10 necrosis, 10 fibrocartilage formation, 10 or degradation at the periphery, 26 despite the production of thicker cartilage tissue. 23 Beyond the microstructure, biochemical and mechanical properties of native cartilage were also either reached or maintained through 6 months and were comparable to previously reported values.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Color images available online at www.liebertpub.com/tea perichondrial layer were consistent with previous research, 3,6,10,12,23 and a continuous elastin network was found similar to only one other tissue-engineered ear study at a comparable time point. 23 In contrast to other long-term studies, auricular constructs at 6 months displayed no signs of osteophyte development, 6,10 necrosis, 10 fibrocartilage formation, 10 or degradation at the periphery, 26 despite the production of thicker cartilage tissue. 23 Beyond the microstructure, biochemical and mechanical properties of native cartilage were also either reached or maintained through 6 months and were comparable to previously reported values.…”
Section: Discussioncontrasting
confidence: 57%
“…25 Although our previous study demonstrated the potential of utilizing photogrammetric and CAD/CAM methods to produce patient-specific molds and constructs, the long-term stability (greater than 3 months) of the developing tissue in vivo has not been verified. In general, few studies utilizing complete human ear geometries have exceeded this time point, 3,6,10,12,23,26 and none of these featured a collagen scaffold. Additionally, the biochemical composition of these constructs must be characterized.…”
mentioning
confidence: 99%
“…Interestingly, this term seems to have “off-label” uses in the literature. For instance, by implantation of an avascular construct, such as a three-dimensional (3D) auricular cartilage construct (von Bomhard et al, 2013) or a tracheal allograft (Vranckx et al, 2014), into a vascular territory for a period, the avascular construct would be revascularized and could be transferred as a composite flap for tissue defect reconstruction (Fig. 3B).…”
Section: Bone Graft Prefabrication Following the Ivb Principle: Basicmentioning
confidence: 99%
“…This method was first described by Erol and Spira, who successfully constructed a prefabricated skin graft in rats using an AVL between femoral vessels (Erol and Spira, 1980). Employing the AVL strategy, formation of a significant neovascular network and new tissue, such as cartilage tissue (von Bomhard et al, 2013), cardiac tissue (Morritt et al, 2007), and muscle tissue (Bach et al, 2006), originating from the arteriovenous fistula have been described.…”
Section: Bone Graft Prefabrication Following the Ivb Principle: Basicmentioning
confidence: 99%
“…The auricular perichondrium contains cartilage progenitor cells necessary for neocartilage formation and promotes the growth of fibrous cells over damaged tissue in cartilage wound healing . It is important for the implantation of autologous or engineered cartilage because the rapid vascular invasion of the perichondrium is essential for supplying oxygen and nutrients to the avascular cartilage layer . It is also necessary for the integration of implants to the native tissue and acts to protect implants from immune response and resorption .…”
Section: Discussionmentioning
confidence: 99%